Karya kita, hak kita untuk semua : panduan hak cipta - Nisah Haron, 1973-; Malaysia; Malaysia (Kuala Lumpur, Malaysia : Al-Ameen Serve Holdings, 2008)
Guidance and practice of intellectual property rights and copyrights in Malaysia.
Includes the texts of: Akta Hakcipta 1987 and Akta Mesin Cetak dan Penerbitan 1984.
Includes bibliographical references (p. 373) and index.
In Malay.
Koleksi sumbangan Dr Mohamad Nasrin Mohamad Nasir.
Keywords: Intellectual property -- Malaysia; Copyright -- Malaysia